PENGARUH BERMAIN POHON HITUNG TERHADAP KEMAMPUAN KONSEP BILANGAN PADA ANAK USIA 5-6 TAHUN DI KELOMPOK BERMAIN SABRINA KID’S 2 KECAMATAN SENAPELAN KOTA PEKANBARU - ', Delima; Jas, Jaspar; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The aim of this study was to know the effect of tree games count towards the introduction of the concept of number of children aged 5-6 years in preschool Sabrina Kid's.2 Senapelan District Pekanbaru .. The population in this study were children aged 5-6 years which consists of class A amounted to 15 people and consists of 7 men and 8 women, the sampling technique used is saturated samples. Data analysis techniques used in this research is the analysis of the t-test, to see the effect of tree games count towards the ability to know the concept of numbers before and after treatment . Data collection techniques in this study using observations. Data analysis techniques used in this research is the analysis of the t-test, to see the effect of tree games count towards kemampuanmengenal concept of numbers before and after treatment using SPSS forwindows Ver.17. based on the results of hypothesis testing is done, the result that the media tree count has a significant impact on the improvement of the ability to know the concept of numbers in children aged 5-6 years in kelompokbermain Sabrina kid's 2 Kecamata Senapelan, Pekanbaru. It can be seen from the results of tests of significance of this difference with the t statistic obtained t = 32.470, df = 14, and the error level of 5% = 2,145, then there is a table t in standard error (32.470> 2.145). Based on the test N-Gain, administration methods Calculate Trees big influence on the ability concept Numbers In children age 5-6 years in early childhood Sabrina kid's 2 Senapelan District, with a value of 76.60% Gain Score.Keywords : Trees Count , Concepts of Numbers .